Enhancing soil fertility: comparative analysis of arecanut monocropping and intercropping with cocoa - Bhat, Ravi; Das, Alpana; Devi, Bhabani; Dutta, Jayashree; Singh, L. S.; Chaithra, M. (Journal of Plantation Crops, 2025)
Soil health is one of the important properties that decide the status of soil fertility. The main objective of the present study was to conduct a comparative analysis of soil health status between arecanutmonocropping and intercropping with cocoa. We analysed and compared the soil pH, bulk density, moisture content, nutrient availability (N, P, K) and microbial diversity of the soil in arecanut+cocoa and arecanutmonocrop system at 0-30 cm and 30-60 cm soil depths. Our investigation revealed that the available macronutrient content reduced with depth in arecanut sole and intercropping with cocoa. At 0-30 cm soil depth, the available nitrogen(N), Phosphorus(P) and potassium(K) in intercropping system was 256 kg/ha,16 kg/ha and 117 kg/ha, respectively, whereas the nutrients were 202 kg/ha, 21 kg/ha and 125 kg/ha in monocropping system. Thesoil organic carbon (SOC) was high in the intercropping system(1.6%.) compared to monocropping (1.0%). Similarly, the HCl extractable micronutrient (Cu, Zn, Fe and Mn) content in the soil was higher in the arecanut intercropping system. The study revealed higher levels of SOC, available P, K, micronutrients, in the arecanut+cocoa system compared to arecanutmonocropping. This suggest that adopting mixed cropping with cocoa can enhance soil fertility.